Diversity and inclusion branding: a five-country comparison of corporate websites - Jonsen, Karsten; Point, Sebastien; Kelan, Elisabeth K. (Academy of Management, 2016)
In the quest to attract talent, organizations must articulate the benefits of having a diverse workforce. By communicating the attractiveness of the workplace, a company increases its exposure to the environment as an employer of choice. In this paper, we conduct a comparative and thematic cross-cultural examination of corporate communication in form of diversity statements. We examine how organizations use diversity statements to attract talent, and discuss how the two strategic areas of diversity and employer branding can be linked in the concept of diversity branding. We examine the websites of 75 major companies in five different countries (France, Germany, Spain, the UK and the United States). Cross-cultural differences and similarities are discussed. We also conclude that the discourse of inclusion is gradually penetrating websites and that branding inclusion can be beneficial in the quest to be an employer of choice.
Keywords: Diversity; inclusion; branding; cross-cultural comparison